Advancement in Conceptualizing Cross-Border Daily Mobility: the Benelux Context in the European Union - Gerber, Philippe (European Journal of Transport and Infrastructure Research, 2012)
Based on specific characteristics of mobility, the cross-border commuter status still has some ambiguities, whether in legal, geographic, economic or more generally in social or cultural terms. This paper aims at providing theoretical advancement to this specific cross-border mobility, especially through the transfer of a theoretical model using a cross-scale analysis based on two complementary concepts. The first corresponds to ‘border confirming’ and is measured at the macro level, including the economic differentials on both sides of the border. The second concept is called ‘border transcending’ and focuses on the individual level. It is based on the assessment of the psychosocial barriers that may fade as the daily practices of the border rise. This exploratory approach is tested within the European context of Benelux. The results, although they cannot be generalised due to a lack of comparable data, offer research perspectives. So far, the existence of a cross-border catchment area, tested on the Belgian cross-border commuters working in Luxembourg, is a reality for many.